Analysis of the Market Structure and Shift-effects in North China Ports - Manlu Liu, Doctoral Student; Seung Ho Kang, Professor; Woo Chul Ahn, Professor (Asian Journal of Shipping and Logistics, 2016)
This study divides the foreign trade traffic of major North China ports into export and import cargoes for the past 10 years. Then, the concentration ratios and shift effects are analyzed in order to determine their relationships with the ports’ competition structures. Here, the HHI, a BCG matrix analysis, and the shift effects are applied as study methods. The results indicate that the oligopoly market structure of major North China ports has gradually decreased. Furthermore, the concentration ratios of import cargoes are higher than those of export cargoes, indicating that competition to attract import cargoes will intensify. Therefore, the effects of the South Korea–China FTA mean that the competition structures of these ports with regard to export and import cargoes are highly likely to be differentiated further over time.